2022
DOI: 10.1021/acsnano.2c06827
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring of Active Sites from Single to Dual Atom Sites for Highly Efficient Electrocatalysis

Abstract: Single atom catalysts (SACs) have been attracting extensive attention in electrocatalysis because of their unusual structure and extreme atom utilization, but the low metal loading and unified single site induced scaling relations may limit their activity and practical application. Tailoring of active sites at the atomic level is a sensible approach to break the existing limits in SACs. In this review, SACs were first discussed regarding carbon or non-carbon supports. Then, five tailoring strategies were elabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
55
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(55 citation statements)
references
References 180 publications
0
55
0
Order By: Relevance
“…Immunology has a lot of acronyms and unfamiliar terms for our journal audience, so we encouraged the authors to develop a vocabulary table to help our readers learn about this fascinating field. Providing vocabulary tables has been a tradition used in ACS Nano ’s review articles since 2015. Additionally, complex concepts can be more readily described in figures rather than text, making them accessible to a broader community. Effective figures need a clean central message, free of distracting excess information.…”
Section: Recent Newsmentioning
confidence: 99%
“…Immunology has a lot of acronyms and unfamiliar terms for our journal audience, so we encouraged the authors to develop a vocabulary table to help our readers learn about this fascinating field. Providing vocabulary tables has been a tradition used in ACS Nano ’s review articles since 2015. Additionally, complex concepts can be more readily described in figures rather than text, making them accessible to a broader community. Effective figures need a clean central message, free of distracting excess information.…”
Section: Recent Newsmentioning
confidence: 99%
“…So far, many impressive review papers have summarized the synthesis, characterization, and catalytic performance of SACs [ 51 , 52 , 53 ]. However, methods for breaking the symmetry of metal-N 4 sites, and the unique electronic structure and CO 2 RR catalytic behavior of asymmetric atom sites, are rarely summarized [ 54 , 55 ].…”
Section: Introductionmentioning
confidence: 99%
“…Single/double atom catalysts (SACs/DACs) supported on such 2D materials not only can boost electrocatalytic performance but also can maximize metal utilization. These catalysts have been studied for various important reactions such as carbon monoxide oxidation, hydrogen evolution reaction, oxygen reduction reaction, nitrogen reduction reaction, and CO 2 RR. Apart from SACs, the DACs loaded on graphene have garnered significant attention both theoretically and experimentally . Notably, introducing a second TM atom in the form of DACs can induce synergistic interactions between metal atoms, thereby triggering enhanced catalyst performance. ,, For example, theoretical studies by Li and co-workers indicated that three DACs (Cu/Mn, Ni/Mn, and Ni/Fe) supported on nitrogen-doped graphene exhibit good CO 2 reduction activity, breaking the original linear relationship between the adsorption strength of COOH* and CO* species . Ren et al successfully synthesized a DAC with Ni/Fe sites anchored on N-doped graphene (Ni/Fe–N 6 –C), where the resulting catalyst achieved an outstanding catalytic efficiency, selectivity, and persistence for CO 2 RR, while their theoretical studies revealed that the synergy between the neighboring Ni/Fe centers accounts for the superior catalytic performance …”
Section: Introductionmentioning
confidence: 99%